Feather mites of the genus Zachvatkinia Dubinin, 1949 (Astigmata: Analgoidea: Avenzoariidae) from Saudi Arabia: A new species and two new records - Negm, Mohamed W.; Nasser, Mohamed G.e.-D.; Alatawi, Fahad J.; Ahmad, Azzam M.al; Shobrak, Mohammed (Zootaxa, 2013)
Feather mites of the family Avenzoariidae (Acari: Astigmata: Analgoidea) are recorded for the first time in Saudi Arabia. A new avenzoariid species, Zachvatkinia (Zachvatkinia) repressae sp. n. (Avenzoariidae: Bonnetellinae), is described from the White-cheeked Tern, Sterna repressa Hartert, 1916 (Charadriiformes: Sternidae). The new species belongs to the sternae group and is closely related to Z. (Z.) chlidoniae Mironov, 1989a. Two more species, Z. (Z.) dromae Mironov, 1992 and Z. (Z.) sternae (Canestrini & Fanzago, 1876), were collected from the Crab Plover Dromas ardeola Paykull, 1805 (Charadriiformes: Dromadidae) and the Sooty Gull Ichthyaetus hemprichii (Bruch, 1853) (Charadriiformes: Laridae), respectively. Among the 18 described species of Zachvatkinia Dubinin, 1949, including the new species, this is the fifth species recorded from a sternid host. The remaining 13 nominal species are associated with birds of the families Diomedeidae, Dromadidae, Hydrobatidae, Laridae, Pelecanoididae, Procellariidae and Stercorariidae. A checklist of world species of Zachvatkinia with data on their distribution and type hosts is also provided.